Correlation Analysis of Anti-Cardiolipin Antibody/D Dimer/C-Reactive Protein and Coronary Artery Lesions/Multiple-Organ Damage in Children With Kawasaki Disease - Xu, Yun-ming; Chu, Yan-qiu; Wang, Hong (Frontiers in Pediatrics, 2021)
Aim: Kawasaki disease (KD) is a systemic vasculitis with unknown etiology. In addition to cardiovascular system involvement, it can also have other multiple organs involved. This study is aimed at investigating the correlation between anti-cardiolipin antibody (ACA)/D dimer/C reactive protein (CRP) and coronary artery lesions (CAL)/multiple-organ lesions in children with KD. Methods: Retrospective analysis was performed in 284 KD/IKD patients from May 2015 to April 2016. Among them, 175 were males (61.6%), with average age of 2 years and 5 months old. Patients were divided into ACA+ group and ACA- group, elevated D dimer group (DDE) and normal D dimer group (DDN), and coronary artery injury (CAL) group and non-coronary artery injury (NCAL) group. Results: ACA was most likely tested positive in younger KD children (p < 0.05). ACA+ and hypoproteinemia were correlated with CAL, thrombocytosis, and granulocytopenia (p < 0.05–0.01). Levels of cTnI and CK in the CAL group were significantly higher than those in the NCAL group (p < 0.05). CAL was more frequently detected in younger patients and patients with prolonged fever, later IVIG treatment, and elevated CRP over 100 mg/l, but there was no statistically significant difference (all p > 0.05). In the KD with DDE group, the incidence of granulopenia, thrombocytosis, myocardial damage, cholestasis, hypoproteinemia, and aseptic urethritis was significantly higher than that in the KD with DDN group (p < 0.05–0.01). However, elevated D dimer was not associated with CAL. CRP elevation was highly correlated with D dimer, but not with CAL. Conclusion: Higher incidence of CAL and myocardial damage occurred in KD patients with positive ACA and hypoproteinemia. In the current study, ACA was only tested for positive and negative, which is a limitation to this study. To further elucidate the association, ACA titers would establish its significance in drawing a conclusion for the significance of ACA in CAL and myocardial damages. In addition, higher incidence of CAL occurred in younger patients. The higher D dimer was associated with increased multiple-organ damage (MOD). CRP was closely correlated with D dimer, but not correlated with ACA and CAL.